Possibilities of developing, adopting and using international standards of financial reporting - Tursunov Tokhir Mirvasikovich (Zien Journals, 2023)
This article is about finance and financial statements, development, adoption and use of international standards of financial statements.
Keywords: standard; profit; finance; cost